Religion, spirituality, and pediatric mental health: a scoping review of research on religion and spirituality in the Journal of the American Academy of Child and Adolescent Psychiatry from 2000 to 2023 - Elzamzamy, Khalid; Naveed, Sadiq; Dell, Mary Lynn (Frontiers in Psychiatry, 2024)
All research and review articles published in JAACAP between 2000-2023 with a focus on R/S themes were retrieved, screened, and appraised for content and extent of focus on R/S (major, minor, incidental). Included articles were assessed for R/S variables and predominant themes.Thirty-two (32) research articles published between 2000-2023 contained sufficient R/S content for inclusion in our study. Only 4 articles had R/S as their major focus. Our analysis suggested a decline in publications with R/S content over the last 24 years. The R/S variables and measurement tools were heterogenous, with religious attendance and religious affiliation being the most frequently measured variables. The predominant themes include the relationships between R/S and psychopathology, suicide, utilization of services, conceptualization of illness, trauma, identity, and coping.